Kajian terhadap Putusan Hakim Nomor 1747/Pid.B/2023/Pn. Sby Ditinjau dari Undang Undang No 17 Tahun 2023 Tentang Kesehatan - Windy Raflyani Dewi; M. Husni Syam (UNISBA Press, 2024)
ABSTRACT. Access to healthcare services is a fundamental right guaranteed by the 1945 Constitution. Hospitals play a crucial role in providing healthcare services, improving and maintaining the health of every individual. The Indonesian state fully regulates health services under Law Number 17 of 2020. Despite the regulations, there have been instances of individuals providing healthcare services under fake identities, leading to various forms of crime in the health sector. This research aims to examine the legal implications for hospitals that employ individuals with fake identities to provide health services. Additionally, it intends to determine the criminal liability of individuals who provide health services with fake identities, according to Law Number 17 of 2023. The research method employed is a normative juridical approach with descriptive analysis. The data was collected through literature studies using secondary data, while the data analysis used qualitative juridical methods. The results of this research indicate that hospitals have a responsibility to compensate for losses incurred due to the negligence of their medical personnel, both administratively, civilly, and criminally. On the other hand, individuals who provide healthcare services in hospitals with fake identities will face criminal charges under the law.